2011
DOI: 10.1590/s0100-879x2011007500088
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-II-induced reactive oxygen species along the SFO-PVN-RVLM pathway: implications in neurogenic hypertension

Abstract: Neurogenic hypertension has been the subject of extensive research worldwide. This review is based on the premise that some forms of neurogenic hypertension are caused in part by the formation of angiotensin-II (Ang-II)-induced reactive oxygen species along the subfornical organ-paraventricular nucleus of the hypothalamus-rostral ventrolateral medulla pathway (SFO-PVN-RVLM pathway). We will discuss the recent contribution of our laboratory and others regarding the mechanisms by which neurons in the SFO (an imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 54 publications
3
70
0
Order By: Relevance
“…These data suggest the involvement of the NO-sGC-cGMP pathway in the relaxant response induced by Oxime S1. In a similar way, Chalupský et al and Veras et al [13,14] demonstrated that the effects of several non-aromatic substituted oximes derivatives involve the NO-sGC-cGMP pathway.…”
Section: Oxime S1 Produces Vasorelaxation Via Activation Of the No-sgmentioning
confidence: 79%
See 1 more Smart Citation
“…These data suggest the involvement of the NO-sGC-cGMP pathway in the relaxant response induced by Oxime S1. In a similar way, Chalupský et al and Veras et al [13,14] demonstrated that the effects of several non-aromatic substituted oximes derivatives involve the NO-sGC-cGMP pathway.…”
Section: Oxime S1 Produces Vasorelaxation Via Activation Of the No-sgmentioning
confidence: 79%
“…Previous studies aiming to evaluate the vascular effects induced by oximes were performed in arteries without endothelium suggesting the involvement of the NO-cGMP pathway [13,14]. The aim of the present study was to investigate the cardiovascular effects produced by a new synthetized oxime, the 3-hydroxy-4-(hydroxyimino)-2-(3-methylbut-2-enylnaphtalen-1(4H)-one (Oxime S1, Figure 1), which is a semi-natural naphthoquinone derivative of lapachol extracted from Tabebuia avallanedae Lor.Ex.Gris (Bignoniaceae), which formula is shown bellow.…”
Section: Introductionmentioning
confidence: 99%
“…3A). Such decrease is associated with an increase of NADPH oxidase activity and generation of ROS Braga et al 2011). Coconut oil combined with exercise training improved baroreflex sensitivity in hypertensive rats.…”
Section: Discussionmentioning
confidence: 95%
“…Several studies have shown that there a strong association between hypertension and the formation of reactive oxygen species (ROS) Braga et al 2011;Mei et al 2014). The generation of ROS is involved in cardiovascular autonomic dysfunction and reduction in baroreflex sensitivity Guimarães et al 2012;Nishi et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Critical to this regulation is the peptide angiotensin II (ANG II), which can elicit increases in sympathetic outflow and blood pressure in normotensive rats by acting via its type 1 receptors (AT 1 R) in the PVN (9,11,36). Further, in animal models of neurogenic hypertension such as the spontaneously hypertensive rat, it is clear that overactivity of ANG II/AT 1 R in the PVN makes a significant contribution to the raised blood pressure seen in these animals (2,10,16,18). Until recently, investigations focused on the direct neuronal actions of ANG II via AT 1 R in the PVN and whether these effects are enhanced in hypertension (5,6,23).…”
mentioning
confidence: 99%